Correlation between functional and structural properties of flexible pavement - Mohmad Barudin, Nurzahrin; Yaacob, Haryati; Abd Hassan, Norhidayah; Warid, Mohd Naqiudin; Idham, Mohd Khairul; Ismail, Che Ros; Md Nor, Hasanan; Hainin, Mohd Rosli; Mohamad, Azman; Afiqah, R N; Ayob, Mohd Fairullazi; Putrajaya, Ramadhansyah (2018)
The functional properties and structural properties are very important in order to evaluate and determine the pavements performance. In pavement condition assessment, monitoring and measurement on the functional and structural properties of the pavement are really needed in order to determine the remaining life of the pavement before any rehabilitation work can be done. This study had further looked on the correlations between these functional and structural properties on a flexible pavement. The study had collected 1198 numbers of functional properties data namely International Roughness Index (IRI), rut depth and texture depth. While for structural properties, 120 numbers of elastic modulus and 12 numbers of California Bearing Ratio (CBR) data has been measured. The functional properties were measured by using Multi Laser Profiler (MLP), while the structural properties were collected by using Falling Weight Deflectometer (FWD) and Dynamic Cone Penetrometer (DCP). The data collection was done along 60 km of asphalt pavement road. Regression analysis shows that the coefficient of determination, R2 obtained for all parameter is near to 0. These results generally conclude that there are no correlations between the functional properties and structural properties on a flexible pavement.